Gender digital inequalities in Argentina during the COVID-19 pandemic: an analysis of differential access to, use of and skills in digital technologies (Praxis Educativa, 2024)
The article studies the ways in which digital inequality reinforced the reproduction of gender inequalities under the COVID-19 pandemic. Based on a national survey applied in Argentina between 2020 and 2021, it analyses how gender differences in terms of access to devices, connectivity and development of digital skills resulted in greater difficulty among women for developing care and pedagogical accompaniment tasks and for teleworking. Thus, it is questioned whether the flexible nature of the latter entails an opportunity for female employment.
Keywords: digital inequality; gender inequalities; pandemic; telework; education